Genetic identification of Anisakis spp. (Nematoda: Anisakidae) from cetaceans of the Southwestern Atlantic Ocean. Ecological and zoogeographical implications - Irigoitia, M. M.; Palomba, M.; Braicovich, P. E.; Lanfranchi, A. L.; Denuncio, P. E.; Gana, J. C. M.; Mattiucci, S.; Timi, J. T. (Parasitology Research, 2021)
Adult Anisakis Dujardin, 1845 were found in two specimens of killer whale Orcinus orca and one specimen of franciscana Pontoporia blainvillei stranded from off the coast of Buenos Aires Province, Argentina. Genetic identification of the nematodes (N = 144) was performed by sequence analysis of the mitochondrial (mtDNA cox2) and the nuclear (nas 10 nDNA) gene loci. Anisakis pegreffii and Anisakis berlandi were detected in the two individuals of O. orca, while Anisakis typica and A. pegreffii were identified in P. blainvillei.Morphological and morphometric analysis also carried out on adult specimens of A. pegreffii and A. berlandi has allowed to underlining the usefulness of genetic/molecular markers in their recognition. This represents the first record of A. pegreffii in O. orca and P. blainvillei and of A. berlandi in O. orca. This is also the first sympatric and syntopic occurrence, as adults, of A. pegreffii and A. berlandi from the Austral Region of the Atlantic Ocean waters. These results provide insights into the knowledge of the host ranges and geographical distribution of these parasites in the basin waters of the region. Pontoporia blainvillei showed low abundance values of infection with Anisakis spp., which is the general pattern for coastal dolphins in the area, whereas O. orca harboured higher abundance of Anisakis spp. than those previously recorded among cetacean species in the Argentine Sea. Differences in the Anisakis spp. distribution and their parasitic loads, observed among the three host specimens, are discussed in relation to the oceanographic parameters, as well as to the host ecology. The usefulness of genetic/molecular markers in the recognition of adults of the sibling species A. pegreffii and A. berlandi with considerable overlapping in morphometric and morphological characters was underlined. The distribution of Anisakis species from Southwestern Atlantic waters is discussed in relation to their value as indicators for studies on the zoogeography of their hosts at a regional-scale ...